2017
DOI: 10.1002/ente.201600618
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Electrical, and Electrochemical Characteristics of LnBa0.5Sr0.5Co1.5Fe0.5O5+δ (Ln=Pr, Sm, Gd) as Cathode Materials in Intermediate‐Temperature Solid Oxide Fuel Cells

Abstract: Layered perovskite oxides have received great attention as prospective cathode materials for intermediate‐temperature solid oxide fuel cells (IT‐SOFCs) because of their high electrical conductivities and fast oxygen kinetics. Herein, we focus on the structural, electrical, and electrochemical properties of layered perovskites LnBa0.5Sr0.5Co1.5Fe0.5O5+δ (LnBSCF, Ln=Pr, Sm, and Gd) as a cathode material for IT‐SOFCs. Among the evaluated perovskites, PrBa0.5Sr0.5Co1.5Fe0.5O5+δ (PBSCF) showed the highest electrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The value of bulk oxygen anion diffusivity as obtained from theoretical calculations is lesser by 2 orders of magnitude compared to the experimentally measured selfdiffusion coefficient of PBSCF. 61 This in general is the case with MD simulations where the diffusion coefficients of oxygen anions in the perovskite and double perovskite structured materials are reported to be significantly different when compared to the experimentally measured values. 62−64 However, noteworthy here is the trend in the diffusivity values calculated using the same method and potentials.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
“…The value of bulk oxygen anion diffusivity as obtained from theoretical calculations is lesser by 2 orders of magnitude compared to the experimentally measured selfdiffusion coefficient of PBSCF. 61 This in general is the case with MD simulations where the diffusion coefficients of oxygen anions in the perovskite and double perovskite structured materials are reported to be significantly different when compared to the experimentally measured values. 62−64 However, noteworthy here is the trend in the diffusivity values calculated using the same method and potentials.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
“…For instance, there exists a controversy in considering PrBa 0.5 Sr 0.5 Co 1.5 Fe 0.5 O 6−δ to be a layered double perovskite. The authors reported the discussed compound to be tetragonal, possessing the P 4/ mmm space group (S.G.), although there exists evidence that its structure can be interpreted in terms of cubic S.G. Pm 3 ̅m , corresponding to a simple perovskite with a disordered A-sublattice . Also, no reliable data on the defect structure and chemical expansion peculiarities of PrBa 0.5 Sr 0.5 Co 1.5 Fe 0.5 O 6−δ are presented in the literature, which makes it difficult to interpret the electrochemical properties of oxides at elevated temperatures .…”
Section: Introductionmentioning
confidence: 99%
“…Among these double perovskite oxides, PrBa 0.8 Ca 0.2 Co 2 O 6−δ (PBCC) has been widely studied due to its high activity for the oxygen reduction reaction (ORR) and good stability against CO 2 under oxidative conditions . However, the large mismatch in the thermal expansion coefficients (TECs) of PBCC (23.03 × 10 –6 K –1 ) and state-of-the-art O 2 -conducting electrolytes (such as Y 0.15 Zr 0.85 O 1.93 (YSZ, 10.5 × 10 –6 K –1 ); Gd 0.2 Ce 0.8 O 1.90 (GDC, 12.5 × 10 –6 K –1 ); La 0.8 Sr 0.2 Ga 0.9 Mg 0.1 O 3– x (LSGM, 10.4 × 10 –6 K –1 )) needs to be addressed. , To drastically prolong the lifetime of a cathode while maintaining high electrocatalytic activity for the ORR, various approaches have been explored, which either optimize the cathode material or modify its microstructure. One effective strategy is the adoption of composite cathodes mixed with GDC or Sm 0.2 Gd 0.8 O 1.90 (SDC) electrolyte, which can promote the compatibility between fuel cell components and prevent crack formation. However, the gas transport path is extended and potentially blocked with the increased thickness of the cathode . Another current research trend is partial substitution of perovskite B-site Co atoms with transition metals (such as Fe, Ni, and Mo), which has proven to be an effective method for prolonging the lifetime of the cathode. Furthermore, the TEC of PBCC is reported to decrease from 23.03 × 10 –6 to 17.95 × 10 –6 K –1 as Fe doping increases from 0 to 50 mol % .…”
Section: Introductionmentioning
confidence: 99%